Language Night 2020 - Butkevičiūtė, Veronika; Zubaitienė , Vilma; Lisauskaitė , Agnė (Vilnius University Proceedings, 2020)
Language Night 2020 is aiming to present a very versatile as well as a fascinating phenomena of Spoken Language. Authors of Language Night 2020 in a briliant manner describe Informal Language in the context of various foreign languages: la langue français, polish, finnish and many others. It gives to readers a wonderful opportunity to rethink language’s border (probably it might be necessary to push it further slightly or the opposite). Moreover, our Collection of Articles suggest to all of us to expand our knowledge on Spoken Language and to experience it together.